UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN TEMBELEKAN (Lantana camara Linn) TERHADAP PERTUMBUHAN Staphylococcus aureus dan Escherichia coli: Antibacterial Activity Test of Tembelekan (Lantana camara Linn) Leaf Extracts on the growth of Staphylococcus aureus and Escherichia coli - Gaby Maulida Nurdin (Biology Department, Mathematics and natural science, Tadulako University, 2021)
This study aimed to determine the effect of concentration ethanol extract from tembelakan leaf (Lantana camara Linn) on bacteria growth of Staphylococcus aureus and Escherichia coli. Extraction was done by maceration using ethanol 96% and then separated using rotary evaporator. Antibacterial activity test of the ethanol extract by Well agar diffusion method. Variation in crude extract saponin used in this study was 5%, 10%, 15%, 20%, 25% and positive controls were used for comparison with Amoxicilin and Chloramphenicole concentration of 25 µg/mL and DMSO as a negative control. The results of antibacterial activity test is indicated by the formation of growth inhibitory region S. aureus and E. coli. The result of growth inhibitory regions was analyzed by One way ANOVA. One way ANOVA test results indicate that there are effects of ethanol extract concentration of tembelekan leaf (L. camara Linn) against S. aureus and E. coli. Effective concentration of ethanol extract tembelekan leaf (L. camara Linn) when compared with positive control to inhibit the growth of S. aureus and E. coli is at 25% with a relatively strong antibacterial activity. Test with phytochemicals screening method which is showed that tembelekan leaf contains the flavanoid, saponins, and tannins compounds as antibacterial